Follicular development status and profile of 17Î² estradiol and cortisol levels during spawning cycle in Oreochromis mossambicus (Peters) - Ganesh, C. B. (Indian Journal of Fisheries, 2014)
In this study, the duration of different phases of the ovarian cycle, the pattern of follicular development and profile of serum levels of 17Î² estradiol (E2) and cortisol were determined in female tilapia, Oreochromis mossambicus. Five oocyte developmental stages, namely chromatin-nucleolous, perinucleolar, cortical alveolar, vitellogenic and early maturation stages were identified. The mean number of stage I (previtellogenic) follicles showed continuous proliferation irrespective of phases of the ovarian cycle, while the stage II (previtellogenic) follicles increased significantly (p<0.05) until the end of vitellogenic phase (day 18) compared to previtellogenic phase (day 6), followed by a significant decrease at the end of prespawning phase (day 23), and a significant increase during the postspawning phase (day 26) (p<0.05). The mean number of stage III (previtellogenic) follicles decreased significantly on day 6 compared to day 1, but increased significantly later through the postspawning phase except for a short decline during prespawning phase. The recruitment of stage IV (vitellogenic) follicles occurred between days 13-18; however their number declined significantly (p<0.05) by the end of prespawning phase compared to vitellogenic phase. The progressive increase in the mean number of stage V (early mature) follicles were noticed only prior to spawning. Furthermore, despite high gonadosomatic and hepatosomatic indices, the serum E2 levels were significantly lower at the end of prespawning phase compared to vitellogenic phase, whereas the serum cortisol levels rose at the end of vitellogenic phase and remained significantly high until postspawning phase compared to previtellogenic phase (p<0.05). These results are helpful to understand the roles of hormonal and environmental factors in regulation of ovarian activity during the spawning cycle in a continuously breeding fish such as O. mossambicus.